INTEGRATING MODELS CHARACTER EDUCATION IN HISTORY LEARNING - Dyah Kumalasari (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2022)
This article is the result of the 3rd year research. The research was designed into two phases (three years). The first stage has obtained results in the form of identification of the method of learning History in high schools in Yogyakarta, as well as whether or not character education has been integrated into the learning process. Based on this identification, a model of integrating character education into history learning in high school was found and a limited trial was carried out at MAN 1 Yogyakarta. In the second year, the developed model was implemented in three selected schools, namely SMAN 9 Yogyakarta, SMAN 8 Yogyakarta, and SMAN 6 Yogyakarta. In the third year, the dissemination of research results was carried out through training and mentoring activities for history teachers who are members of the DIY Province history MGMP.The dissemination of the research results was carried out in several activities, namely: (1) inviting 100 history teachers who are members of the DIY provincial history MGMP; (2) participated as a co-speaker in an international seminar at the University of Indonesia with the theme "interpreting of Indonesian Independence admist Global Changes in Historical Perspective". Based on the results of the socialization that had been carried out, input was obtained that in general the model was very well received by history teachers. In addition to receiving training, teachers also receive learning videos and guidebooks for implementing learning models in schools. Some things that can be noted during socialization activities are: (1) the role playing model for the material about the events surrounding the proclamation of independence was considered by the teacher to be very appropriate and applicable in the learning process in order to explore the positive characters of each character played; (2) the students who happened to be assigned to play the characters looked excited and enthusiastic, even at SMAN 9 the characters Sukarno, Wikana, and Sukarni seemed to really live their roles; (3) students who just watched, looked enthusiastic to follow until the end of the round and showed interested and not bored faces because the performance time was not long, only about 30-45 minutes, their enthusiasm was also shown when without being coordinated they stood up and enthusiastically sang Indonesia Raya anthem together during the flag-raising scene; (4) the success or failure of this role playing model is applied in the learning process very much depends on the role of the teacher. Teachers who direct and motivate optimally from the start will be followed by student enthusiasm. The success of this model is also determined by the way the teacher reflects on every event that has been played by his students.